DIALEKTIKA SYARIAT ISLAM DAN NEGARA - Sirajuddin M (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
This study  aims  to understand the  teachings (shari’a) of Islam  and  explore its positionin the  national life level. The method of this study is a historical-philosophical study that aims to unravel the root of the dynamic histories of Islam  in Indonesia and  the ideology  of Pancasila in order to seek the intersection of both in an effort to strengthen the understanding and  practice of Pancasila. The result  of this study is that  Islam  as religious values  can be a source of national (law) development based on the ideology of Pancasila. With Islamic values, then the national development can run better and more maximally because of the relationship between Islamic religious values and national development, so it can realize the welfare of the birth and mind